Legal Aspects of Development of Single Market of Financial Services in the European Union - M. P. Lukinskaya (Московский журнал международного права, 2011)
The article reviews the main development stages of legal regulation of financial services in the European Union along with the sources of European finance law and its specifics. The emphasis is given to the analysis of core directives regulating investment services. Evolvement and development of main concepts of single market of financial services is being traced down, and specifics of principle of mutual recognition are being analyzed. The article characterizes the role of the Court of Justice of the European Union in affirmation of freedoms which are necessary for performance of investment and financial services in EU. Additionally the case-law of the Court of Justice of the European Union in the area of financial services is being examined hereunder. The author determines the key concepts of an investment firm and “European passport” for performance of investment services as well as makes assessment of a conduct of business of investment firms. The article points out the way whereby the home country control principal regulates business of financial institutions which provide financial services beyond borders of a country of registration. The special emphasis is given by the author to the Financial Services Action Plan as to one of the most essential documents for development of integrated financial market in EU. The article is being finalized by an overview of current investment strategy in the European Union.